Identification of hard-to-recover reserves of Ugra oil - S. G. Kuzmenkov; Yu. A. Kuzmin; P. A. Stulov; R. Sh. Ayupov; V. I. Bulatov; N. O. Igenbaeva; V. I. Isaev; G. A. Lobova (Геофизический журнал, 2019)
More than 70 % of the reserves of Yugra oil fields, which are in development and at various stages of study, are classified as hard-to-recover (HTR). Active involvement in the development of HTR will prevent the decline and stabilize production in the most important oil-producing region. Compliance with state economic interests and stimulation of subsoil users require a clear and adequate formulation of the criteria for attributing deposits to an HTR, involving preferences and tax incentives. The geological-field analysis of the balance of hydrocarbon reserves and of the licensing agreements for the subsoil use of Yugra was carried out in the context of the criteria for identification of deposits with the HTR, recommended by the Central Commission of the Rosnedra of the Russian Federation (2005), also in the context of the Federal Law of the RF and the Tax Code of the RF (2013―2014), defining the criteria and objects of the HTR, differentiation of mineral extraction tax rates. The analysis has shown that at present some objects of the category of HTR do not require tax incentives, and for other objects that have not been previously classified as HTR, tax incentives should be introduced. The complex of criteria for identification of deposits of the HTR «RAC RUS named after V. I. Shpilman», compiled on the basis of criteria approved by the Central Commission for Reserves of the Russian Federation, which takes into account the geological and technological parameters of deposits given in the state balance, and the current Classification of oil reserves of the Russian Federation became the result of the analysis. According to the results of the analysis, it was suggested: to exclude from the category of HTR the terrigenous deposits of the «anomalous cut» of the Bazhenov Formation and the uncomplicated Neocom deposit; to include in the category of HTR deposits of the Achimov Formation and the Pre-Jurassic Complex. The deposits of the Achimov Clinoform and the Pre-Jurassic Complex of particular interest were described in more detail. The deposits of the Achimov Clinoform and the Pre-Jurassic Complex of particular interest were described in more detail.